1996
DOI: 10.1055/s-2008-1035178
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Messung von intraokularem Gas

Abstract: Observations of the level of gas meniscus at retina with indirect ophthalmoscopy is an accurate method for estimating intraocular gas volumes. It extends the range of measurement significantly beyond the pupil. Tables based on a mathematical model convert disc diameters to milliliters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The ability to detect a closed MH or the status of the foveal detachment or schisis by the SD‐OCT was evaluated, and the pre‐ and postoperative factors that affected the OCT images were investigated. The volume of intravitreal gas was estimated by the level of the inferior gas meniscus at the retina observed with an indirect ophthalmoscope in a sitting position 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to detect a closed MH or the status of the foveal detachment or schisis by the SD‐OCT was evaluated, and the pre‐ and postoperative factors that affected the OCT images were investigated. The volume of intravitreal gas was estimated by the level of the inferior gas meniscus at the retina observed with an indirect ophthalmoscope in a sitting position 16 …”
Section: Methodsmentioning
confidence: 99%
“…The volume of intravitreal gas was estimated by the level of the inferior gas meniscus at the retina observed with an indirect ophthalmoscope in a sitting position. 16…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The volume of intravitreal gas was determined by one of the authors (MI) based on the level of the inferior gas meniscus at the retina observed with an indirect ophthalmoscope in a sitting position [10, 11]. …”
Section: Methodsmentioning
confidence: 99%